1995
DOI: 10.1111/j.1365-2265.1995.tb02645.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute desmopressin and of long‐term thyroxine replacement on haemostasis in hypothyroidism

Abstract: Summary OBJECTIVE Hypothyroidism can be complicated by bleeding symptoms such as easy bruising, menorrhagla and sometimes even a severe bleeding tendency with fatal outcome. Usually there is a prolonged bleeding time, or a low plasma concentration of coagulation factor VIII (FVIII) or von Willebrand factor (vWF). The aim of the present study was to investigate the acute haemostatic effect of desmopressin in hypothyroid patients. Another aim was to study the long‐term effect of thyroxine replacement on the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…We retrieved full copies of 28 potentially appropriate studies and four abstracts (neither manuscript nor abstract of one paper could be retrieved) [8]. After excluding five articles not meeting the prespecified inclusion criteria, a total of 23 plus four abstracts were included in the final analysis [3,9–34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We retrieved full copies of 28 potentially appropriate studies and four abstracts (neither manuscript nor abstract of one paper could be retrieved) [8]. After excluding five articles not meeting the prespecified inclusion criteria, a total of 23 plus four abstracts were included in the final analysis [3,9–34].…”
Section: Resultsmentioning
confidence: 99%
“…Erfurth et al. investigated the acute haemostatic effect of desmopressin (DDAVP) and the long‐term effect of thyroxine replacement therapy on the plasma concentrations of coagulation factors in 10 hypothyroid patients [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired von Willebrand's disease is very likely to be type 1 in all cases because of a normal ratio of von Willebrand's factor antigen to ristocetin cofactor r [31]. The underlying defect could possibly be a decreased synthesis of von Willebrand factor in the absence of adequate levels of thyroxine [32], and thyroxine replacement corrects these abnormalities [31, 33]. Erfurth and group have demonstrated that desmopressin immediately reduced bleeding time, enhanced platelet adhesiveness, and significantly increased plasma concentrations of factor VIII and von Willebrand's factor and hence may be valuable for the acute treatment of bleeding or as cover for surgery in a setting of myxedema crisis or severe hypothyroidism [33].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The underlying defect could be decreased synthesis because of lack of triiodothyronine stimulation which is a possible explanation since our patient recovered from bleeding manifestations and normalised his platelets and APTT spontaneously after treatment with levothyroxine 1. The vasopressin analogue desmopressin has been shown to be a successful drug in the acute treatment of bleeding in hypothyroidism 6. Our patient also presented with anaemia.…”
Section: Discussionmentioning
confidence: 66%